Analisis Newman dalam Menyelesaikan Soal Statistika Ditinjau dari Metakognitif Tacit Use - Raras Kartika Sari (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
The study was conducted to analyze student errors in the statistical problem-solving process using Newman in terms of metacognitive tacit use. The research method used is qualitative method. Data analysis used is the analysis of the results of the test, questionnaire analysis and analysis of interview transcripts. Based on the results of the study, it was concluded that the subjects of tacit use metacognitive categories did not know their weaknesses in the learning process, gave inconsistent answers, had little confidence, focused only on answers and not on the process. Subjects with tacit use metacognitive categories made mistakes in solving statistical problems almost at all stages of Newman. Newman's error analysis consists of reading errors, comprehension errors, transformation errors, process skills errors, encoding errors. The subject is wrong in interpreting the symbol, the subject cannot determine what is known and asked about the question, the subject does not write detailed calculation steps, and the subject cannot conclude the final answer to the problem solving. Errors in completing the test questions occur because the subject does not re-check the answers given in the problem.